Manajemen risiko dengan metode hazard identification risk assessment and determining control aspect impact (HIRADC-AI) pada pekerja pengepul dan pemulung - Ro’is, Rachmy Rosyida; Sulistyorini, Anita; Laksana, Dian Puspitaningtyas; Pramudya, Dandy Arie; Sucita, Ni Made DwiAstini; Bahari, Bima Sutan Putra; Rachmanissa, Tiara (Holistik Jurnal Kesehatan, 2025)
Background: Pulosari Scavenger Village is a densely populated settlement located along the railway tracks. Most residents work as scavengers and scrap metal collectors in a scrap metal warehouse. Therefore, Pulosari Scavenger Village poses potential hazards for workers and the community. Purpose: To identify hazards and control occupational health and safety risks. Method: This was a descriptive observational study using a cross-sectional design, documentation, interviews, and analysis using the Hazard Identification, Risk Assessment, and Determining Control - Aspect Impact (HIRADC-AI) method, conducted directly at each work stage in Pulosari Scavenger Village. Results: The total number of hazards identified from eight work activities with potential hazards was 52, consisting of six high-risk, 36 medium-risk, and eight low-risk. The hierarchy of controls represents a potential hazard control strategy in Pulosari Scavenger Village, primarily through administrative controls and the use of personal protective equipment. Conclusion: The main sources of hazards include chemical exposure, poor ergonomic practices, unorganized working conditions, lack of personal protective equipment (PPE), and inadequate infrastructure. The most feasible risk control measures are administrative controls and consistent use of PPE, while elimination and substitution are not feasible due to the nature of the work.   Keywords: Collectors; Hazard Identification Risk Assessment And Determining Control Aspect Impact (HIRADC-AI); Risk Management; Scavengers.   Pendahuluan: Kampung pemulung merupakan salah satu pemukiman padat penduduk yang terletak di bantaran rel kereta api. Masyarakat kampung pemulung rata-rata memiliki pekerjaan sebagai pemulung dan pengepul barang bekas pada gudang besi tua. Sehingga, kampung pemulung memiliki potensi bahaya untuk pekerja dan masyarakat pada kampung tersebut. Tujuan: Untuk mengidentifikasi bahaya dan pengendalian risiko keselamatan dan kesehatan kerja. Metode: Penelitian observasional deskriptif dengan desain cross sectional, dokumentasi, wawancara serta analisis menggunakan metode Hazard Identification Risk Assessment and Determining Control - Aspect Impact (HIRADC-AI) yang dilakukan secara langsung pada setiap tahapan pekerjaan pada kampung pemulung Pulosari. Hasil:  Jumlah risiko bahaya dari 8 aktivitas pekerjaan dengan potensi bahaya sebanyak 52, yang terdiri 6 potensi risiko tinggi, 36 potensi risiko sedang, dan 8 potensi risiko rendah. Hierarki kontrol merupakan upaya yang dapat dilakukan untuk mengendalikan potensi bahaya pada Kampung Pemulung Pulosari, terutama pada upaya pengendalian administratif dan penggunaan alat pelindung diri.  Simpulan: Sumber utama bahaya meliputi paparan bahan kimia, praktik ergonomi yang buruk, kondisi kerja yang tidak tertata, kurangnya penggunaan alat pelindung diri (APD), serta infrastruktur yang tidak memadai. Upaya pengendalian risiko yang paling memungkinkan dilakukan adalah pengendalian administratif dan penggunaan APD secara konsisten, sementara eliminasi dan substitusi tidak dapat diterapkan karena sifat pekerjaan tersebut.   Kata Kunci: Hazard Identification Risk Assessment And Determining Control Aspect Impact (HIRADC-AI); Manajemen Risiko; Pemulung; Pengepul.